Nutritional Literacy and Fast Food and Junk Food Consumption Behavior among Overweight Adolescents - Monika, Monika; Simbolon, Demsa; Yuliantini, Emy (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Overweight among adolescents has become an important public health concern because it increases the risk of various degenerative diseases and long-term health complications. Poor dietary patterns, particularly frequent consumption of fast food and junk food, are often associated with limited nutritional literacy among adolescents. This study aimed to examine the effect of nutritional literacy on fast food and junk food consumption behavior among overweight adolescents. This study employed a quasi-experimental design with a pre-test and post-test control group approach. The sample consisted of 46 overweight adolescents from SMA Negeri 7 Bengkulu City, divided into an intervention group (23 participants) and a control group (23 participants), selected using purposive sampling. The intervention group received nutritional literacy education using a flipchart accompanied by explanations, while the control group received education through leaflets without explanation. The study variables included nutritional literacy, fast food and junk food consumption habits, body weight, and height. Data were analyzed using independent t-test, paired t-test, Mann–Whitney test, and Wilcoxon test. The results showed a significant increase in knowledge scores before and after the nutritional literacy intervention (p = 0.014). There was a significant difference in the mean change in attitude scores between the intervention and control groups (p = 0.0001), with a higher improvement observed in the intervention group. In addition, there was a significant difference in the mean change in fast food and junk food consumption habits between the two groups (p = 0.043). In conclusion, nutritional literacy education is effective in improving knowledge, attitudes, and reducing fast food and junk food consumption behavior among overweight adolescents.Keywords: nutritional literacy; consumption behavior; overweight